A critical analysis on Wright and Lander's article: 'Collaborative group interactions of students from two ethnic backgrounds'. Issue 2 (2018) - Lau, Yui-yip
In this paper, the author provides a critical analysis of Wright and Lander's (2003) article, 'Collaborative group interactions of students from two ethnic backgrounds'. Taking an empirical research approach, Wright and Lander apply a quantitative methodology to investigate a possible scenario for student interaction within different collaborative groups. Focusing on Wright and Lander's research, this study will briefly review the evolution of educational research since the nineteenth-century and classify our methodological approach in light of that. The remaining part of this study proceeds as follows: Sections 2 and 3 provide a synopsis of the selected research, and then identify its main strengths. A critical evaluation of Wright and Lander's research is presented in Section 4, including theory, research design, methods and researcher values, and possible improvements to the study and some conclusions are given in Section 5.